Hydrogel Actuator with a Built‐In Stimulator Using Liquid Metal for Local Control. (14th April 2020) - Matsubara, Ken; Tachibana, Daiki; Matsuda, Ryosuke; Onoe, Hiroaki; Fuchiwaki, Ohmi; Ota, Hiroki
Abstract : Hydrogel actuators, comprising gels that convert external stimuli into mechanical motion for actuation, are attracting attention for their promising applications, such as in robotics. The driving force is the absorption or release of water or another solvent, which results in swelling and shrinking motions, leading in turn to more complex functionalities. However, practical hydrogel actuators that can be controlled locally, such as ones that allow local actuation around the joints in rigid‐bodied robots, do not exist. Herein, the driving target of a thermo‐responsive hydrogel, poly( N ‐isopropyl acrylamide), is integrated with the stimulation module using a liquid metal. The stimulation module provides heat as an external stimulus to the hydrogel actuator. The motion of the actuator is triggered by the heat supplied by an ultrasoft hydrogel coil, with liquid metal surrounding the driving target. The heat generated by current flowing through the liquid metal changes the temperature only around the desired part of the actuator, which enables the electrical control of an individual part of the hydrogel actuator. The concept of integrating the driving target and stimulator is expected to facilitate functional movement of actuators and expand the range of potential applications of hydrogels. Abstract : Herein, an electrically driven gel actuator using a liquid metal spring and temperature‐responsive gel is proposed. The actuations are triggered by heat generated by current flows through the liquid metal spring. The shrinking and bending movements of the actuators are realized by reducing the volume of the temperature‐responsive gel inside the spring.